How accounting students within the Thuthuka Bursary Fund perceive academic support offered at one South African university - Ontong, J.M.; De Waal, T.; Wentzel, W. (South African Journal of Higher Education, 2020)
Recent academic performance of students in their chartered accountancy professional examinations has been under scrutiny by the business community in South Africa, especially examination performance amongst Black, Coloured and Indian (BCI) students (SAICA, 2019a; Ryan, 2019). Noting the importance of preparing higher education students for future professional examinations, this study focused on Thuthuka Bursary Fund (TBF) students in accounting. The study participants were all from BCI groups whilst the study aimed to gain insight into TBF students’ perceptions regarding the value of two academic support structures. These structures involved additional tutorials, only offered to TBF students and individual learning program sessions, offered to all accounting students. The study aimed to understand the support format required to equip students to better prepare for examinations. Student perceptions were analysed to identify those aspects which could potentially make the offered support structures more conducive to the learning needs of students. Understanding student perceptions about the effectiveness of academic support is critical in promoting the study success of students and meeting their learning objectives. The study found that certain aspects of academic support are judged to positively contribute to students’ learning, while others can be improved upon. Students seem to prefer smaller support class sizes, language-specific facilitators, support classes being scheduled during normal class hours instead of after hours, an emphasis on exam writing techniques and, to a lesser extent, course content being covered. The findings suggest more regular student feedback about the academic support offered which could result in revisions to existing support structures. Such revisions might contribute to better assistance to students, potentially increasing their performance – also in continued professional learning after graduation.